Analisis Komparatif Pelayanan Indomaret Dan Alfamart Di Tais Kecamatan Seluma - Aprianti, Jesi; Tito Irwanto; Melinda, Tri Febrina; Putri , Lydia Gustina (Jurnal Multidisiplin, 2025)
One of the retail businesses that serve basic needs and daily needs is minimarket. The minimarket business is one of the businesses classified as a retail business that has great potential. The presence of a minimarket business offers an alternative for consumers who need products. The purpose of this study is to analyze the comparison of services between Indomaret and Alfamart in Tais, Seluma District. This type of research uses quantitative comparative nature. The data collection method in this study used a questionnaire technique, with a sample of 100 people from Indomaret and 100 respondents from Alfamart Muara in Tais, Seluma Sub-District. The results showed that the first hypothesis showed that the results of data processing showed that the original sample value was 0.162 (positive), the value t-count was 1.850 (>1.96) and the values of p met the requirements, namely 0.035 <0.05. So that H1 in this study is accepted. It can be concluded that the services of Indomaret Muara Dalam Seluma has a positive and significant effect. The second hypothesis shows that the results of data processing show that the original sample value is 0.666 (positive), the value t count is 7.759 (> 1.96) and p values meet the requirements, namely 0.000 < 0.05. So that H2 in this study is accepted. It can be concluded that the services of Alfamart Muara Dalam Seluma has a positive and significant effect. Based on the results of the calculation obtained F count 179.748>F table 2.65 which means that the variables Indomaret (X1), Alfamart (X2) and Service Quality (Y) simultaneously have a positive and significant effect in Tais, Seluma Sub-District.